Early selection in rubber tree plants by using microtest tapping - Marques, José Raimundo Bonadie; Gonçalves, Paulo de Souza (Pesquisa Agropecuaria Brasileira, 2014)
The relationship among yieldings obtained from Mendes early test tapping (MTP), Hamaker-Morris-Mann test (HMM) and annual regular tappings was studied. The objective was to evaluate efficiency of the MTP in selection of young ortets and ramets from the rubber tree (Hevea spp.) breeding programme conducted at the Djalma Bahia Experimental Station in Bahia State, Brazil. The tests were conducted in two differents field experiments. In the first field, before budding, the ortets in the nursey stage were submitted to MTP test tapping. After budding, 43 clones were transplanted to the field. Later, at the fourth and seventh year of growth they were submited to HMM test and regular tapping respectively. In the second field at one year of age 43 different clones were evaluated by MTP test. Nine years later they were resigned to regular tapping during five years consecutivelly. The results archieved showed inexistence of relationship with MTP in both experiments. Otherwise the HMM was highly correlated with annual regular tappings. A discerning analyse of the correlations among annual regular tappings showed that is posible to select clones for yielding based in the first annual regular tapping.